Study to Explore Psychological Aspects of COVID-19 Among Patients in Pakistan - Farhan, Ali Farhan; Laraib Imran; Ali Hassan; Anum Munir; Afaque Ahmed; Sania Khurshid (Technium Social Sciences Journal, 2020)
COVID-19 outbreak is affecting the world population and has emerged as a global pandemic, started from the city Wuhan, China in December 2019. The physical and mental health that is being affected due to the trauma and suffering from COVID-19 leads to additional associated factors. It has been pointed by the physicians that mental health implications of COVID-19 are still unknown. In this study we analyzed the extent of response under the ambit of anxiety, depression and physical well-being of persons who have recovered from the novel COVID-19 in Pakistan. The rapid spread of COVID-19 has lead to health emergencies in mental health institutes implemented by the Governments of different countries. Considering the social impact, the outbreak leaves large and growing financial loses as business and trade industries are severely affected due to lockdown. Such situations are likely to increase the stress among the population and patients. Patients with co-morbids, and old age were mostly affected. Individuals from different districts of Pakistan were included in this study and total 104 designed questionnaires were distributed to the affected persons who have recovered from COVID-19.